Congestive Heart Failure Exhibited Higher BMI With Lower Energy Intake and Lower Physical Activity Level: Data From the National Health and Examination Nutrition Survey - Xu, Tianyu; Zhou, Haobin; Ma, Zhuang; Zhang, Hao; Zeng, Qingchun; Xu, Dingli; Zhang, Yuhui; Zhang, Jian (Frontiers in Cardiovascular Medicine, 2021)
Background: Despite that nutritional deficiency existed in congestive heart failure (CHF), there is a large amount of CHF patients suffering from obesity. This study aimed to identify the differences for increased BMI or obesity in CHF patients. Methods: This cross-sectional study included adults from the National Health and Nutrition Examination Survey 2007–2016. Differences were compared between CHF participants vs. non-CHF participants, and BMI ≥ 30 kg/m2 vs. BMI < 30 kg/m2 CHF participants. Results: CHF participants were with higher BMI, lower energy and macronutrient intake, lower physical activity level and longer rest time, and lower hematocrit and hemoglobin level (all P < 0.05) than non-CHF participants. The prevalence of BMI ≥ 30 kg/m2 in participants with CHF was 53.48%. There was no significant difference observed in energy and macronutrient intake between CHF participants with BMI ≥ 30 kg/m2 or <30 kg/m2. The water intake (P = 0.032), sedentary time (P = 0.002), and hematocrit (P = 0.028) were significantly different between CHF with BMI ≥ 30 kg/m2 and with <30 kg/m2. Conclusion: Compared with non-CHF participants, CHF participants exhibited higher BMI with lower energy and macronutrient intake, lower physical activity level, longer rest time, and hemodilution with lower hematocrit and hemoglobin level. Among CHF participants with BMI ≥ 30 kg/m2, higher sedentary time and hematocrit were observed.